Análisis comparativo de la habilidad de solución de problemas en estudiantes iniciales y finales de ingeniería - Aguilar-Villarreal, Arlethe Yarí; Vargas-Moreno, Argelia; Hernández-Landa, Leonardo Gabriel (Universidad Autónoma de Nuevo León, 2020)
The present descriptive comparative study analyzes thesproblem-solving skills of engineering students in northernsMexico, exploring the parity between the skills of thosesstudents who are starting off against those who aresfinishing the academic program. Factors such as self perception of academic performance, work experience andsinclination to entrepreneurship showed an impact onsstudents' problem-solving skills. The independent variablesanalyzed in this research, as well as their respectivesinternal scales, included: a) problem-solving skill, b)ssolution commitment, c) solution confidence, and d)ssolution methodology. The study showed no significantsdifference in problem-solving skills between thespopulations of engineering students starting off and thosesfinishing the academic program. It is recommended tosexpand this study so that factors that affect the ability tossolve problems can be better identified to encourage thescontinuous improvement of the academic program and tosfurther advance a comprehensive education of futuresstudents.